Raptor mediates the selective inhibitory effect of cardamonin on RRAGC-mutant B cell lymphoma - Ying Liu; Yanting Zhu; Huajiao Chen; Jintuo Zhou; Peiguang Niu; Daohua Shi (BMC, 2023)
Abstract Background mTORC1 (mechanistic target of rapamycin complex 1) is associated with lymphoma progression. Oncogenic RRAGC (Rag guanosine triphosphatase C) mutations identified in patients with follicular lymphoma facilitate the interaction between Raptor (regulatory protein associated with mTOR) and Rag GTPase. It promotes the activation of mTORC1 and accelerates lymphomagenesis. Cardamonin inhibits mTORC1 by decreasing the protein level of Raptor. In the present study, we investigated the inhibitory effect and possible mechanism of action of cardamonin in RRAGC-mutant lymphoma. This could provide a precise targeted therapy for lymphoma with RRAGC mutations. Methods Cell viability was measured using a cell counting kit-8 (CCK-8) assay. Protein expression and phosphorylation levels were determined using western blotting. The interactions of mTOR and Raptor with RagC were determined by co-immunoprecipitation. Cells overexpressing RagC wild-type (RagCWT) and RagC Thr90Asn (RagCT90N) were generated by lentiviral infection. Raptor knockdown was performed by lentivirus-mediated shRNA transduction. The in vivo anti-tumour effect of cardamonin was assessed in a xenograft model. Results Cardamonin disrupted mTOR complex interactions by decreasing Raptor protein levels. RagCT90N overexpression via lentiviral infection increased cell proliferation and mTORC1 activation. The viability and tumour growth rate of RagCT90N-mutant cells were more sensitive to cardamonin treatment than those of normal and RagCWT cells. Cardamonin also exhibited a stronger inhibitory effect on the phosphorylation of mTOR and p70 S6 kinase 1 in RagCT90N-mutant cells. Raptor knockdown abolishes the inhibitory effects of cardamonin on mTOR. An in vivo xenograft model demonstrated that the RagCT90N-mutant showed significantly higher sensitivity to cardamonin treatment. Conclusions Cardamonin exerts selective therapeutic effects on RagCT90N-mutant cells. Cardamonin can serve as a drug for individualised therapy for follicular lymphoma with RRAGC mutations.